Endothelial Soluble Factors Mediate Differentiation of Circulating Endothelial Precursors. Issue 2 (August 2015) - Musilli, Claudia; Paccosi, Sara; Graziani, Gabriele; Caporale, Roberto; Gelli, Anna Maria Grazia; Parenti, Astrid
Abstract : Abstract: Although endothelial progenitor cells have been used in clinical trials with promising preliminary results, the mechanism by which these cells interact with vascular wall cells and ischemic tissues remains unclear. We have previously reported that human coronary artery endothelial cells cocultured with peripheral blood mononuclear cell (PBMC) can stimulate their early differentiation toward a pre-endothelial phenotype. This study was aimed to assess possible soluble factors, released from the coculture, and involved in endothelial progenitor cell differentiation. Among cytokines and chemokines measured by means of Milliplex assay, interleukin (IL)-6, IL-8, endothelial growth factor, and CCL-2 were released in cocultures, and those levels were significantly higher than that found in human coronary artery endothelial cells or in PBMCs alone. To check their involvement in PBMC differentiation, blocking experiments with neutralizing antibodies were performed. Flow cytometry analysis confirmed an impairment of PBMC differentiation toward a pre-endothelial phenotype when IL-6, IL-8 and with a lesser extent CCL-2 were blocked. These data add a new insight into the mechanisms by which endothelial precursors interact with vascular wall, thus suggesting future directions in understanding and treating ischemic injury.